Effect of different levels of neutral detergent fiber in starter diets on the performance, ruminal fermentation, and structural growth of Holstein calves - Ren, Chunyan; Bi, Yanliang; Tu, Yan; Guo, Yanli; Bing, Rui; Wang, Jiqing; Diao, Qiyu (Frontiers in Veterinary Science, 2025)
We evaluated the effect of starter diets with four levels [12.85, 19.91, 26.99, and 34.04% of dry matter (DM)] of neutral detergent fiber (NDF) on the growth, ruminal fermentation, and structural growth of Holstein calves. A total of 60 Holstein calves [42.3 ± 1.1 kg, body weight (BW)] aged 1–3 days were randomly assigned to 4 treatments: a starter diet with a dry matter basis without hay forage, 12.85% NDF; a starter diet with 14% forage, 19.91% NDF; a starter diet with 28% forage, 26.99% NDF; and a starter diet with 42% forage, 34.04% NDF. The hay forage (alfalfa hay and oat grass) was pelleted together with the concentrate to provide the calves, which had ad libitum access to water and starter feed throughout the experiment. Following weaning at 70 days, the calves continued on their respective diets until the trial termination at 112 days of age. The average daily gain (ADG) decreased linearly (p = 0.02) with increasing dietary NDF concentration. The starter intake and total dry matter intake (TDMI) increased quadratically (p = 0.02 and p = 0.03, respectively) with increasing NDF concentration in the starter diets, with maximal values observed at 26.99% NDF. Feed efficiency (FE) exhibited a decreasing trend with elevated NDF levels in the starter formulations during the post-weaning period, whereas diets containing 12.85 and 19.91% NDF diets maintained superior efficiency. Notably, the NDF intake showed a linear increase (p < 0.01) during both the pre- and post-weaning periods as the starter NDF levels escalated. The pH value exhibited either a linear or quadratic relationship with increasing dietary NDF levels at 112 days of age. The valerate concentrations showed a linear decreasing trend with increasing dietary NDF levels at 112 days of age. The total volatile fatty acid (TVFA) concentrations increased linearly with increasing dietary NDF levels. Elevating dietary NDF levels showed a linear reduction in the final body weight (BW) and weaning BW. The calf body length exhibited a linear decrease with increasing NDF levels, with the 12.85 and 19.91% NDF diets yielding greater values at 112 days of age. The blood beta-hydroxybutyric acid (BHBA) concentration was linearly elevated by higher dietary NDF levels at 70 days of age. Under the experimental conditions, the dietary NDF level of 12.85% or 19.91% enhanced the average daily gain (ADG), BW, and structural growth parameters. These findings indicate that the dietary NDF content below 26.99% constitutes the optimal range for Holstein calves aged 1–3 months.